Microcystin-LR Does Not Alter Cell Survival and Intracellular Signaling in Human Bronchial Epithelial Cells - Brózman, Ondřej; Kubickova, Barbara; Babica, Pavel; Laboha, Petra (Toxins, 2020)
Changes in ecological and environmental factors lead to an increased occurrence of cyanobacterial water blooms, while secondary metabolites-producing cyanobacteria pose a threat to both environmental and human health. Apart from oral and dermal exposure, humans may be exposed via inhalation and/or swallowing of contaminated water and aerosols. Although many studies deal with liver toxicity, less information about the effects in the respiratory system is available. We investigated the effects of a prevalent cyanotoxin, microcystin-LR (MC-LR), using respiratory system-relevant human bronchial epithelial (HBE) cells. The expression of specific organic-anion-transporting polypeptides was evaluated, and the western blot analysis revealed the formation and accumulation of MC-LR protein adducts in exposed cells. However, MC-LR up to 20 μM neither caused significant cytotoxic effects according to multiple viability endpoints after 48-h exposure, nor reduced impedance (cell layer integrity) over 96 h. Time-dependent increase of putative MC-LR adducts with protein phosphatases was not associated with activation of mitogen-activated protein kinases ERK1/2 and p38 during 48-h exposure in HBE cells. Future studies addressing human health risks associated with inhalation of toxic cyanobacteria and cyanotoxins should focus on complex environmental samples of cyanobacterial blooms and alterations of additional non-cytotoxic endpoints while adopting more advanced in vitro models.
Keywords: mikrocystiny; p38 Mitogen-Activated Protein Kinases; buněčné linie; mořské toxiny; Bronchi; lidé; Epithelial Cells; bronchy; Extracellular Signal-Regulated MAP Kinases; Microcystins; signální transdukce; Signal Transduction; mitogenem aktivované proteinkinasy p38; Cell Line; Organic Anion Transporters; Marine Toxins; Cell Survival; viabilita buněk; přenašeče organických aniontů; extracelulárním signálem regulované MAP kinasy; epitelové buňky; Humans